Combate moral: O moralismo ostentatório nos discursos sobre operações policiais e “violência urbana” - Vittorio da Gamma Talone; Alexandre Werneck; Caio Neves (Interseções)
This paper aims to analyze the different ways in which the summoning of force, through a model of behaviorwe call ostentatious moralism, act as a way of selectively trivializing death in an environment of the social representation of urban violence. To this end, we analyze how readers of news reports on police operations respond to those they interpret, within the scope of the articles, as bearers of a violent sociability and those supportive of them. The research is based on the tabulation of 100 articles about police operations in Rio de Janeiro’s favelas from 2019 to 2022 on the website of the newspaper Extra and, from that, more than 50,000 comments on them, both in the website’s comment section and on their page on the social network Facebook. We carried out a detailed semiotic analysis of 472 of these comments, in which ways of power enforcement and moral tenacity and intransigence are manifested. We concluded that social actors, in an environment we described as marked by an “imperative of opinion”, summon force through expressive ways of moral simplification, notably through ridiculing and embarrassing their opinion opponents.